Recombination parameters of point defects in dislocation-free silicon single crystals - Talanin, V.I.; Talanin, I.E. (Functional Materials, 2006)
The recombination parameters of the point defects dynamics (recombination barrier, recombination time, recombination factor) at high and low temperatures are discussed proceeding from the heterogeneous mechanism of grown-in microdefects formation and transformation. The cooling-induced decomposition of the oversaturated solid solution of point defects in silicon follows two mechanisms: vacancy-type and interstitial-type ones. Therefore, vacancies and intrinsic silicon interstitials find drains in the form of background impurity atoms like oxygen and carbon. The formation of intrinsic point defect-impurity pairs is the dominant process at temperatures near the silicon melting point. Рассмотрены рекомбинационные параметры модели динамики точечных дефектов (рекомбинационный барьер, рекомбинационное время, рекомбинационный фактор) для высоких и низких температур, исходя из гетерогенного механизма образования и трансформации ростовых микродефектов. Вызванный охлаждением распад пересыщенного твердого раствора точечных дефектов в кремнии протекает по двум механизмам: вакансионному и межузельному. Поэтому вакансии и собственные межузельные атомы кремния находят стоки в виде атомов фоновых примесей, таких как кислород и углерод. Образование пар "собственный точечный дефект - примесь" является доминирующим процессом при температурах, близких к точке плавления кремния. Розглянуто рекомбiнацiйнi параметри моделi динамiки точкових дефектiв (рекомбiнацiйний бар'єр, рекомбiнацiйний час, рекомбiнацiйний фактор) для високих та низьких температур, виходячи з гетерогенного механiзму утворення i трансформацiї ростових мiкродефектiв. 3а рахунок охолодження розпад пересиченого твердого розчину точкових дефектiв у кремнiї вiдбувається за двома маханiзмами: вакансiйним та мiжвузловинним. Тому вакансiї i власнi мiжвузловиннi атоми кремнiю знаходять стоки у виглядi атомiв фонових домiшок, таких як кисень та вуглець. Утворення пар "власний точковий дефект - домiшка" є домiнуючим процесом при температурах, близьких до точки плавлення кремнiю.